Back to the future? The long view of probation and sentencing. (September 2018) - Raynor, Peter
This article reviews the history of the probation service's contribution to sentencing and revisits the changing theories and understandings that have influenced this role at different times. Through most of its history probation was seen as an alternative to punishment and required the consent of the probationer. Since the 1990s these fundamental assumptions have been changing, and the article explores some of the social and political context of these changes. It argues (with the help of John Augustus, Charles Dickens and others) that the probation service's input of social information into sentencing has been a contribution to social justice, but recent changes in the reporting role have made this much more difficult. Finally, some suggestions are made about how probation's traditional input into sentencing might be restored.